The Effect of E-Learning on Learning Motivation in Islamic Religious Education Subjects: Pengaruh E-Learning Terhadap Motivasi Belajar Mata Kuliah Pendidikan Agama Islam - Fitria, Dessy; Saifudin, Saifudin; Zaman, Badrus (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to determine the effect of the use of E-learning learning on learning motivation of PTKIN students from various provinces in Indonesia, through testing differences in learning motivation between students who use E-learning and students who do not use E-learning. The method used in this study uses a quantitative method. The population and sample used in this study were students from various provinces in Indonesia with 103 respondents, data collection was done using online questionnaires and assisted by using the SPSS application to test the significance of the influence of independent variables (use of e-learning) on ​​the dependent variable (learning motivation college student). SPSS test results show that the use of E-learning has a positive and significant effect on the learning motivation of millennial students today. Can be known from the results of this study showed an F-test of 89,543 with a significant value of 0,000. The use of E-learning in learning has a considerable influence in the success of millennial students learning in Indonesia because it can be seen that the millennial generation has started to get bored and bored with face-to-face learning without pauses. The use of E-learning has an effect on student motivation because in this system students are required to be more creative and independent in seeking information from various sources anytime and anywhere. Thus, learning using E-learning can be applied and maximized because it is proven to increase PTKIN's millennial students' learning motivation from various provinces in Indonesia.